Polyphenols alleviate metabolic disorders: the role of ubiquitin-proteasome system - Gu, Wei; Wu, Guohuo; Chen, Guijie; Meng, Xianghui; Xie, Zhongwen; Cai, Shanbao (Frontiers in Nutrition, 2024)
Metabolic disorders include obesity, nonalcoholic fatty liver disease, insulin resistance and type 2 diabetes. It has become a major health issue around the world. Ubiquitin-proteasome system (UPS) is essential for nearly all cellular processes, functions as a primary pathway for intracellular protein degradation. Recent researches indicated that dysfunctions in the UPS may result in the accumulation of toxic proteins, lipotoxicity, oxidative stress, inflammation, and insulin resistance, all of which contribute to the development and progression of metabolic disorders. An increasing body of evidence indicates that specific dietary polyphenols ameliorate metabolic disorders by preventing lipid synthesis and transport, excessive inflammation, hyperglycemia and insulin resistance, and oxidative stress, through regulation of the UPS. This review summarized the latest research progress of natural polyphenols improving metabolic disorders by regulating lipid accumulation, inflammation, oxidative stress, and insulin resistance through the UPS. In addition, the possible mechanisms of UPS-mediated prevention of metabolic disorders are comprehensively proposed. We aim to provide new angle to the development and utilization of polyphenols in improving metabolic disorders. FIGURE 1. Graphic abstract: Mechanisms of polyphenols target UPS to prevent metabolic disorders. Polyphenols alleviate metabolic disorders by modulating E3 ubiquitin ligases and the 26S proteasome to mitigate insulin resistance, oxidative stress, abnormal lipid metabolism, and inflammatory responses through regulating the ubiquitin-proteasome system.